Effect of transition metals on the crystal field in CeCo0.4Fe0.6Ge3. (February 2023) - Skokowski, P.; Synoradzki, K.; Reiffers, M.; Dzubinska, A.; Rols, S.; Arapan, S.; Legut, D.; Toliński, T.
Abstract: We present an investigation of the influence of the 3 d elements, Co and Fe, on the interactions between magnetic Ce atoms in the CeCo0.4 Fe0.6 Ge3 alloy, the member of the CeCo1− x Fe x Ge3 series. The investigated alloy crystallizes in the noncentrosymmetric tetragonal BaNiSn3 -type structure (space group I 4 mm, No. 107), in which the Co and Fe atoms occupy the same 2 a position. The close vicinity to the quantum critical point for this alloy was indicated based on previous reports and confirmed by our low temperature resistivity measurements presented in this article. The role of Co and Fe atoms in this alloy was deduced from the scheme of the crystal field levels employing inelastic neutron scattering, specific heat, and magnetic susceptibility. For the analysis, samples LaCoGe3, LaFeGe3, and LaCo0.4 Fe0.6 Ge3 were used as non-magnetic analogs. The obtained results for CeCo0.4 Fe0.6 Ge3 alloy were compared with those for CeCoGe3 and CeFeGe3 compounds to emphasize the observed changes in physical properties. The specific heat results are supported by the first-principles calculations. The analysis indicated that the excitation levels of Ce ions are different for the Co- and Fe-rich neighborhood. Based on this information, we can conclude that the 3 d elements provide the same energies of RKKY and Kondo interactions for the nearest Ce ions, but their energies for the further ions are lowered due to the presence of other 3 d elements. Graphical abstract: Image 1 Highlights: Resistivity measured down to 500 mK in the NFL region of the CeCo1- x Fe x Ge3 series. Verification of NFL power law for resistivity in various magnetic fields. Lattice contribution to specific heat confirmed by ab-initio calculations. Results of inelastic neutron scattering, specific heat, and magnetic susceptibility. CF levels determined based on experimental data.